Sociopsychology of anomy - Caycho Caja, Aaron (2019)
The present article shows the conceptualizations about the anomie from the initial theoretical approaches of Durkheim, Parsons, Merton and later interdisciplinary approaches. Likewise, an epistemological analysis of the concept oriented to delimit its sociological and psychological implications is carried out. Finally, a socio-psychological proposal is made for the study of social phenomena based on the concepts used by Luhmann and Ortiz.